Lubrication Mechanism of Phosphonium Phosphate Ionic Liquid in Nanoscale Single‐Asperity Sliding Contacts. Issue 17 (12th July 2020) - Li, Zixuan; Dolocan, Andrei; Morales‐Collazo, Oscar; Sadowski, Jerzy T.; Celio, Hugo; Chrostowski, Robert; Brennecke, Joan F.; Mangolini, Filippo
Abstract: While phosphonium phosphate ionic liquids (ILs) have been evaluated as additives for engine oils owing to their excellent physico‐chemical properties, miscibility with hydrocarbon fluids, and promising tribological properties, their lubrication mechanism is still not established. Here, atomic force microscopy (AFM) nanotribological experiments are performed using diamond‐like carbon‐coated silicon tips sliding on air‐oxidized steel in neat trihexyltetradecylphosphonium bis(2‐ethylhexyl)phosphate IL. The AFM results indicate a reduction in friction only after the removal of the native oxide layer from steel. Laterally resolved analyses of the steel surface chemistry reveal a higher concentration of bis(2‐ethylhexyl)phosphate ions adsorbed on regions where the native oxide is mechanically removed together with a change in surface electrostatic potential. These surface modifications are proposed to be induced by a change in adsorption configuration of bis(2‐ethylhexyl)phosphate anions on metallic iron compared to their configuration on iron oxide together with a reduction of surface roughness, which lead to the formation of a densely packed, lubricious boundary layer only on metallic iron. Abstract : Atomic force microscopy nanotribological tests and laterally‐resolved surface analyses are combined to establish a phenomenological model for the lubrication mechanism of phosphonium phosphate ionic liquid. The ability of this ionic liquid to reduce friction derives from the generation of a densely‐packed boundary layer, whose formation depends on the adsorption configuration of phosphate ions on iron oxide and metallic iron.